Segregation texts: Riksdag's open data: Committee on EU Affairs - Språkbanken Text (University of Gothenburg, 2024)
Documents from the Committee on EU Affairs

Dokument från EU-nämnden, bland annat möteskallelser, föredragningslistor, protokoll och skriftliga samråd med regeringen
Segregationstexter: Riksdagens öppna data: EUN
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik